2022
DOI: 10.1002/ejp.1983
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophizing as a prognostic factor for pain and physical function in the multidisciplinary rehabilitation of fibromyalgia and low back pain

Abstract: Background: Quantitative data on longitudinal associations between catastrophizing and pain or physical function are patchy. The study aimed to quantify the prognostic value of catastrophizing for pain and function in fibromyalgia and low back pain before and after rehabilitation. Methods: The associations of state and change on the Multidimensional Pain Inventory (MPI) Pain severity scale, the Short Form 36 (SF-36) Physical functioning scale and the Six-Minute Walking Distance (6MWD) with the Coping Strategie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…Treatment goals directed to lessen pain catastrophizing and depression levels should be promoted to reduce the impact of pain in FMS patients' daily function. Indeed, in a recent study, pain catastrophizing has been put forwarded as a potential prognostic factor for rehabilitation associated changes in pain and self-rated physical function (this last in a less extent) in FMS and low back pain [ 71 ]. At this regard, acceptance and commitment therapy (ACT), which is considered an effective therapeutic approach for FMS [ 72 , 73 ], has shown medium-large effect size in the reduction of the FMS impact, measured by the FIQ [ 74 77 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment goals directed to lessen pain catastrophizing and depression levels should be promoted to reduce the impact of pain in FMS patients' daily function. Indeed, in a recent study, pain catastrophizing has been put forwarded as a potential prognostic factor for rehabilitation associated changes in pain and self-rated physical function (this last in a less extent) in FMS and low back pain [ 71 ]. At this regard, acceptance and commitment therapy (ACT), which is considered an effective therapeutic approach for FMS [ 72 , 73 ], has shown medium-large effect size in the reduction of the FMS impact, measured by the FIQ [ 74 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Behavioural Neurology and self-rated physical function (this last in a less extent) in FMS and low back pain [71]. At this regard, acceptance and commitment therapy (ACT), which is considered an effective therapeutic approach for FMS [72,73], has shown medium-large effect size in the reduction of the FMS impact, measured by the FIQ [74][75][76][77].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This also appears to be the case in FMS, where highly complex multivariate models can perform reasonably well, but their clinical utility may be limited, and where simpler models do not seem adequate [135]. Similarly, familiar variables such as catastrophizing are shown to significantly predict some outcomes, but not all, and not typically with strong effects [136]. It may be that current treatment designs and group-based research methods are limited for identifying who will benefit and who will not [137].…”
Section: The Future Of Psychology In Fibromyalgiamentioning
confidence: 92%
“…The MPI is a reliable and valid self-report instrument that measures the impact of pain on the patient’s life, quality of social support and general activity. 21 , 22 It has been previously shown that this condition-specific instrument, especially the three-item MPI pain severity domain, is highly responsive to changes in pain sensation during a 4-week rehabilitation program in patients with chronic pain. 23 For this reason, patients will be asked to “Rate the level of your pain at the present moment” from 0 (no pain) to 6 (very intense pain); “On average, how severe was your pain in the last week?” from 0 (not at all severe) to 6 (extremely severe); and “How much suffering do you experience because of your pain?” from 0 (no suffering) to 6 (extreme suffering).…”
Section: Methodsmentioning
confidence: 99%